2021
DOI: 10.3390/app11125584
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Dynamic Device with Uniform Shear Stress Distribution for Microscopy and Permeability Measurements

Abstract: Neurology has always been one of the therapeutic areas with higher attrition rates. One of the main difficulties is the presence of the blood–brain barrier (BBB) that restricts access to the brain for major drugs. This low success rate has led to an increasing demand for in vitro tools. The shear stress, which positively affects endothelial cell differentiation by mimicking blood flow, is required for a more physiological in vitro BBB model. We created an innovative device specifically designed for cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In contrast, in our work, cells were cultivated at the bottom of a single channel. In the future, this experiment could be reproduced after cultivating hCMEC/D3 cells on a dual chamber microfluidic device composed of a semi-permeable membrane [ 91 ]. Effects of SS on BMEC of various origins was previously reported: de Stefano et al reported no clear differences between claudin-5, occludin, and ZO-1 expression/localization under static and flow conditions in derived human brain microvascular endothelial cells (dhBMECs) [ 50 ], whereas SS triggered the translocation of ZO-1 with an increased junctional intensity in primary porcine BMEC[ 92 ] and a stronger immunoreactivity of occludin and ZO-1 at cell borders in primary bovine BMEC[ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in our work, cells were cultivated at the bottom of a single channel. In the future, this experiment could be reproduced after cultivating hCMEC/D3 cells on a dual chamber microfluidic device composed of a semi-permeable membrane [ 91 ]. Effects of SS on BMEC of various origins was previously reported: de Stefano et al reported no clear differences between claudin-5, occludin, and ZO-1 expression/localization under static and flow conditions in derived human brain microvascular endothelial cells (dhBMECs) [ 50 ], whereas SS triggered the translocation of ZO-1 with an increased junctional intensity in primary porcine BMEC[ 92 ] and a stronger immunoreactivity of occludin and ZO-1 at cell borders in primary bovine BMEC[ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…After successful seeding, the membrane was placed in the engineered microfluidic slide, clamped with the clamping system and was then attached to the fluidic unit of the pump. Cells were maintained under shear stress levels of 4–15 dyn/cm 2 , which are considered comparable to those reported in brain capillaries in vivo [ 37 , 38 , 39 , 40 , 41 ]. At the start of the experiment, the shear stress level was maintained at 4 dyn/cm 2 , as a greater shear stress led to the detachment of the cells from the membrane.…”
Section: Methodsmentioning
confidence: 66%
“…The principle is similar to the contact Transwell cultivation, with BMECs covering the inside of the lumen, while the other cellular components of the NVU are seeded extraluminally. The main advantage of DIV models over static co-cultures is the possibility to induce quasi-physiological shear stress, considered essential for BMECs phenotype modulation [ 92 ]. Other pros include the higher TEER, a relevant parameter when studying molecular/drug passage via the BBB [ 107 ], together with the ability to examine BBB alteration in hypoperfusion and reperfusion conditions [ 108 ].…”
Section: In Vitro Models Of the Human Blood–brain Barriermentioning
confidence: 99%